"Análisis metodológico de la contabilidad de costos y su incidencia en los costos de producción de la empresa SIGCHOLAC ubicada en el cantón Sigchos, período económico 2018" - Andino López, Margoth Isolina (2019)
It is very important for companies to have a cost system to correct the lack of knowledge of the costs involved in production, mainly in the manufacture of cheese. For this reason, the objective of this research project is to analyze methodologically cost accounting and its incidence in the production costs of the SIGCHOLAC company located in the Sigchos canton, Cotopaxi province, economic period 2018, through the systems of costs. In order to fulfill this purpose, the bibliographic and documentary collection was used; techniques such as the application of interviews with the manager of the production department and the observation guide, which was carried out directly in the production line of the factory, all this with the objective of collecting primary information to achieve the cost system. Through the situational diagnosis, a clearer idea of the problem in question was obtained. At the end of the work it was determined that the three systems, have a different methodology to determine the elements of cost, the system for production orders, has as the objective of having an order or production order, where the cost is determined before processing of the product. In what they have to do with the system by processes in each of its subprocesses, it determines these elements and the ABC is divided into the subprocesses in activities and these in inductors, to calculate the real cost of the product. It is concluded in the system for production orders is which generates lower unit cost in the production.